Georges Rouault's (un)popular clown paintings. Issue 3 (3rd July 2018) - Price, Jason
ABSTRACT: During the long career of French painter Georges Rouault (1871–1958), the artist is known to have created around 170 paintings featuring images of popular entertainers, most often circus performers and clowns. Painted in the artist's signature 'messy' style, the clowns depicted often appear out of their performative context and in an unhappy state that seems incongruous with their character. This article makes a case that such an approach falls under the category of (un)popular art, which occurs when artists appropriate and then dismantle popular images in order to construct works of high art. The author argues that while the artist's aesthetic clearly oversees a shift in the cultural status of the clown from popular to elite art, the effects of Rouault's expressionism are strongly dependent upon acknowledging the popular dimensions of the work. Reconceptualising the exchanges between certain cultural forms, such as those between popular culture forms and the avant-garde, as (un)popular offers a productive way of foregrounding the essential contribution popular culture has made to elite culture, and helps redress the historical prejudices which have established the popular as antithetical to works of high art.